Longitudinal Assessment of Depressive Symptoms After Sport-Related Concussion in a Cohort of High School Athletes. (January 2021) - Hammer, Erin; Hetzel, Scott; Pfaller, Adam; McGuine, Tim
Background: The long-term effect of sport-related concussion on mood in adolescent athletes is largely unknown. Hypothesis: Longitudinal measures of depression will worsen acutely after sport-related concussion and improve with concussion symptom resolution. Study Design: Prospective cohort study. Level of Evidence: Level 3. Methods: A population-based sample of 2160 high school athletes from 31 urban, suburban, and rural high schools completed preseason baseline concussion symptom evaluation and Patient Health Questionnaire–9 (PHQ-9) assessments over 2 years. Athletic trainers recorded onset of sport-related concussion, and concussed athletes completed the PHQ-9 assessment within 24 to 72 hours, 7 days, date of return to sport, 3 months, 6 months, and 12 months after sport-related concussion. Scores at each time point were compared to baseline with mixed-effects models and repeated-measures analysis of variance. Sex-based differences were assessed using mixed-effect models. Results: Of the 2160 athletes enrolled in the study, 125 (5.8%; 80 males, 45 females) sustained a sport-related concussion. PHQ-9 scores worsened from baseline at 24 to 72 hours (+1.05; 95% CI, 0.26-1.84; P = 0.003) and 7 days (+0.91; 95% CI, 0.23-1.60; P = 0.006). However, PHQ-9 scores improved from baseline to date of return to sport (−1.38; 95% CI, −2.20 to −0.55; P < 0.001), 3 months (−1.08; 95% CI, −1.88 to −0.28; P = 0.003), 6 months (−1.19; 95% CI, −2.04 to −0.34; P = 0.001), and 12 months after sport-related concussion (−0.76; 95% CI, −1.43 to −0.08; P = 0.028). Female athletes reported more severe concussion symptoms 24 to 72 hours after sport-related concussion compared with male athletes (female, 20.5 [interquartile range (IQR), 10.0-36.2]; male, 9.0 [IQR, 4.0-19.5]; P = 0.003). Neither PHQ-9 scores nor change in PHQ-9 scores differed between male and female athletes at any time point. Conclusion: Sport-related concussion did not worsen longitudinal measures of depressed mood in this cohort of high school athletes. Clinical Relevance: Emotional symptoms are common after sport-related concussion, but typically resolve by return to sport.